Artifical intelligence and international arbitration law: revolution or evolution - Łągiewska, Magdalena (Routledge research in international commercial law, 2026)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape. Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law. This book will be of interest to researchers in the field of international arbitration and commercial law
Keywords: Arbitrage; Artificial Intelligence; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Intelligence artificielle; International commercial arbitration; UNCITRAL Model Law on International Commercial Arbitration (1985)

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (JMAR, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Revue Justice Actulaités, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Effective Conflict Management - International Chamber of Commerce (ICC Publication DRS, 2023)

The Singapore Convention on Mediation: a commentary - Alexander, Nadja; Chong, Shouyu; Giorgadze, Vakhtang (Kluwer Law International, 2022)
Article-by-article commentary
Keywords: Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018)

Règlements d’Arbitrage en vigueur à compter du 1er janvier 2021 et de Médiation en vigueur à compter du 1er janvier 2014 - Chambre de commerce internationale (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Règlement d'arbitrage; Règlement de médiation

Arbitration Rules In force as from 1 January 2021 and Mediation Rules In force as from 1 January 2014 - International Chamber of Commerce (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration rules; MARD; Mediación; Mediation; Mediation rules; Mediação; Médiation

Los medios jurisdiccionales de solución de las controversias internacionales : avances y nuevos retos - Petrova Georgieva, Virdzhiniya (Doctrina Jurídica, 2022)

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Studien zum ausländischen und internationalen Privatrecht, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

Guide de l'arbitrage de l'OMPI - Centre d’arbitrage et de médiation de l'OMPI (OMPI, 2020)

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation

Proceedings of 1st Annual Research Symposium on International Commercial Arbitration - Casoria, Maria (Royal University for Women, 2019)
Keywords: Arbitrage; Arbitragem; Arbitration; Convention on the Recognition and Enforcement; Foreign Arbitral Awards; International Commercial Mediation; International Settlement Agreements; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements; UNCITRAL Model Law

Arbitraje Comercial Internacional. Reconocimiento y Ejecución de Sentencias y Laudos Arbitrales Extranjeros - Paulsson, Jan; Opertti Badán, Didier; Santos Belandro, Rubén; Bouchenaki, Amal; Ojea, Mildred; Rivera, Irma; Caivano, Roque J.; Solís Zelaya, Román; Fernández López, Alberto; Fresnedo de Aguirre, Cecilia; Gosis, Diego B.; Gomm Santos, Mauricio; et al. (IIJ, 2019)
Keywords: Arbitraje Comercial International; Arbitration; Commercial arbitration agreements; Conflict of laws; International arbitration award; Sentences arbitrales étrangères

Règlement d'arbitrage en vigueur à compter du 1er mars 2017, règlement de médiation en vigueur à compter du 1er janvier 2014 - Cour internationale d'arbitrage; Centre international d'ADR (Publication ICC, 2019)
Keywords: Arbitration; Mediation

Proceedings ISDS reform conference 2019: mapping the way forward - Asian Academy of International Law (2019)
Keywords: Dispute settlement; Investment disputes; LAW REFORM; UN Commission on International Trade Law

Guide de l'arbitrage de la CCJA-OHADA - Cour Commune de Justice et d'Arbitrage (CCJA) (OHADA, 2018)

Guide pour le développement des services de médiation et arbitrage - Centre du Commerce International (ITC, 2018)
Keywords: Centre d'arbitrage; Centre de conciliation; Centre de médiation; Gestion; Management

La médiation et l'arbitrage dans l'espace UEMOA : recueil des lois et pratiques - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; UEMOA

La médiation et l’arbitrage de litiges commerciaux dans l’espace UEMOA - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; Médiation

Revista PLMJ Arbitragem : Jurisprudência comentada de 2017 - Coimbra Trigo, Ana; Monteiro, António Pedro Pinto; Heidrich Jaques, Betyna; Góis Coelho, Carla; Carrera, Iñaki; Schmid Moura, Joana; Tornada, João; Júdice, José-Miguel; Caldeira, Leonor; Carvalho, Mariana; Gouveia, Mariana França; Ziegler, Pacôme; et al. (PLMJ Advogados, 2018)

La médiation civile : alternative ou étape du procès ? - Leborgne, Anne (Droit privé, 2018)
Initialement pensé comme une alternative à la solution judiciaire, le recours à la médiation, processus structuré, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l’aide d’un tiers le médiateur, choisi par elles ou désigné avec leur accord par le juge saisi du litige, apparaît aujourd’hui, dans de nombreux procès de droit privé comme une étape du règlement judiciaire. Il en est ainsi, en droit de la famille, en droit de la consommation, en droit commercial mais également désormais, en droit social. Depuis 2015 en effet, le Code de procédure civile impose aux parties à un litige de justifier, lors de l’introduction de l’instance, des diligences entreprises en vue de parvenir à une résolution amiable de leur litige et le juge est lui-même invité à leur proposer une mesure de conciliation ou de médiation à défaut de justification. Un pas de plus a été franchi avec la loi de modernisation de la justice du 18 novembre 2016, dite « Justice 21 », qui a rendue obligatoire la tentative de conciliation ou de médiation pour les petits litiges du quotidien, avant la saisine du juge d’instance. On pouvait dès lors se demander si ce mode de résolution d’un conflit participait de la justice ou s’il s’en distinguait et comment il était accueilli par les justiciables et les praticiens du droit. C’est à ces questions que le colloque des 28 et 29 avril 2017 a cherché à répondre, à partir de l’examen du droit positif et prospectif français et en utilisant le droit comparé, européen et international. Les résistances comme les initiatives pour promouvoir la médiation ont été examinées lors de la première journée de la manifestation. Le deuxième jour a permis de faire point sur l’actualité de la médiation civile dans les différentes branches du droit privé et de mesurer l’influence des règlements européens et de la jurisprudence de la Cour européenne des droits de l’homme sur le développement de ce processus.
Keywords: Code de procédure civile; Cour européenne des droits del'homme; Droit de la consommation; Droit privé; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Médiation familiale; Recours

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Nijhoff International Investment Law Series, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

Guide du secrétariat de la CNUDCI sur la Convention pour la reconnaissance et l’exécution des sentences arbitrales étrangères (New York, 1958) - Commission des Nations Unies pour le Droit Commercial International (Nations Unies, 2017)

Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York, 1958) - UNCITRAL (United Nations, 2015)

L’arbitrage OHADA - Kenfack Douajni, Gaston (Droit OHADA et droits communautaires africains, 2014)
L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a été créée par le Traité de Port-Louis (Ile Maurice) le 17 octobre 1993, modifié à Québec (Canada) le 17 Octobre 2008. L’OHADA a pour but de promouvoir les investissements dans ses 17 États parties à travers la sécurisation juridique et judiciaire de l’environnement des affaires, par la production de normes juridiques, simples, adaptées et modernes en droit des affaires, au nombre desquelles les instruments relatifs à l’arbitrage. Premier ouvrage de la collection droits OHADA et droits communautaires africains, l’Arbitrage OHADA procède à une présentation synthétique et à une analyse exhaustive des instruments OHADA relatifs à l’arbitrage, que sont l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage de l’OHADA (Règlement CCJA). Outre les textes normatifs posant les bases de l’arbitrage OHADA, cet ouvrage met aussi à la disposition du lecteur la jurisprudence de la CCJA et commente les premières applications pratiques de l’arbitrage OHADA. Il est en cela indispensable à tous les praticiens de l’arbitrage OHADA. Mais au-delà, par la réflexion qu’il développe sur les difficultés rencontrées et les espérances suscitées par la mise en œuvre de l’arbitrage OHADA et – en définitive – sur l’apport de l’arbitrage dans le développement du droit OHADA et l’amélioration du climat des affaires en Afrique, cet ouvrage intéresse un public bien plus vaste (Universitaires, Barreau, Magistrature, Opérateurs économiques) et est appelé à constituer la référence en matière d’arbitrage pour l’ensemble des usagers du droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford Monographs In International Law, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

Contratación y arbitraje internacionales - Méndez Silva, Ricardo (Doctrina Jurídica, 2010)
https://archivos.juridicas.unam.mx/www/bjv/libros/6/2776/1.pdf
Keywords: Arbitrage international; Arbitragem; Arbitraje; Arbitraje Comercial International; Arbitration; International commercial arbitration

Différends entre investisseurs et État : Prévention et modes de règlement autres que l’arbitrage - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2010)
Keywords: Différends; Etat; Investisseurs; Modes de règlement; Prevention

Le consentement des parties à l’arbitrage international - Diallo, Ousmane (International, 2010)
Mode juridictionnel privé de règlement des litiges, l’arbitrage offre une alternative à la saisine du juge. Qu’il soit interne ou international, l’arbitrage repose généralement sur le consentement des parties. C’est donc à juste titre que celui-ci a été qualifié de pierre angulaire de l’arbitrage. Effectivement, c’est sur ce consentement que la justice privée s’est longtemps appuyée pour justifier sa légitimité, revendiquer son autonomie et conquérir un nouvel espace de liberté. Solidement porté par le consentement qui lui sert de fondement, l’arbitrage n’a cessé de se développer au point d’apparaître de nos jours comme le mode normal de règlement des litiges du commerce international. On le dit particulièrement adapté au règlement de telle ou telle catégorie de litiges, manière d’affirmer sa vocation à étendre son emprise. Parvenu à l’âge adulte, c’est donc tout naturellement que l’arbitrage cherche à s’affranchir du caractère exceptionnel que lui imprime sa subordination au consentement, lequel apparaît de plus en plus comme un îlot de résistance à son expansion, sinon à son efficacité. Première étude d’ensemble sur la question, le présent ouvrage a le grand mérite d’exploiter au mieux la richesse qu’offre une approche comparative, non seulement pour retracer le rôle important joué par le consentement dans l’évolution de l’arbitrage, mais aussi, et surtout, pour mettre à nu les multiples tentatives en vue de son émancipation de la tutelle des parties. Il en résulte une éclipse momentanée du consentement, qui ravive les contestations de la compétence arbitrale et dévoile à nouveau sa subordination au consentement, facteur de légitimation par excellence de l’arbitrage. C’est dire que le consentement ne fait pas que survivre à ces assauts, il réussit même à prospérer. Autant de questions aussi brûlantes qu’actuelles, sur lesquelles cet ouvrage offre une analyse détaillée et des solutions originales.
Keywords: Arbitrage international; Arbitration; Droit privé; International arbitration; Litige; Règlement des différends

L'arbitrage et les tiers - Boularbah, Hakim; Caprasse, Olivier; Cox, Kristof; Dal, Marc; De Meulemeester, Dirk; Keutgen, Guy; Verbist, Herman; Wautelet, Patrick (Actes du colloque du CEPANI 40 du 28 novembre 2008, 2008)

L'arbitrage et la distribution commerciale - Jardin, Laurent du; Erauw, Johan; Hollander, Pascal; Keutgen, Guy; Matra, Didier; Van Houtte, Hans (Actes du colloque du CEPANI du 17 novembre 2005, 2005)

Conciliation et médiation judiciaires - Joly-Hurard, Julie (Droit privé, 2003)
Keywords: Concilition judiciaire; Médiation judiciaire; Pourparlers judiciaires

Les sociétés et l'arbitrage - Caprasse, Olivier (Bruylant, 2002)

L'exécution des sentences arbitrales en vertu de la Convention de New York : expériences et perspectives - Mazilu, Dumitru; Houzhi, Tang; Kaplan, Neil; Delvolvé, Jean-Louis; Lebedev, Sergeï N.; Paulsson, Jan (Nations Unies, 1999)

La cour d'arbitrage : actualités et perspectives - Andersen, Robert; Delpérée, Francis; Jadot, Benoît; Lejeune, Yves; Rasson-Roland, Anne; Rigaux, Marie-Françoise; Simonart, Henri; Tulkens, François; Van Compernolle, Jacques (Centre d'Etudes constitutionnelles et administratives, 1988)